Factors associated with falls among older persons in Limbang division, Sarawak - Teh, Jo Hun (Universiti Malaysia Sarawak (UNIMAS), 2011)
Ageing brings with it numerous challenges and issues and an increase in degenerative and age related diseases. Degenerative changes due to ageing leads to reduced adaptability to sudden changes in environment or body position and this results in loss of balance and falls. Falls among the older persons is common and often result in serious morbidity and mortality. Falls among older persons are therefore an important public health problem and its true extent and factors associated with it needs to be studied" This cross sectional study assesses the association between falls and socio-demographic factors, extrinsic risk factors, intrinsic risk factors, functional status and determined predictors of falls in this study population. A total of 187 community dwelling older persons were selected by multi-stage sampling of villages within government health clinic operational areas. Five government clinics out of 15 were randomly selected; subsequently five villages per clinic were again randomly selected. Finally, ten respondents were systematically identified from each village. This survey was carried out from November 2010 to February 2011 using face to face interviews. A questionnaire was developed that contained sections on socio-demographic variables and environmental fall risk factors, including falls and circumstances of falls, medical conditions and prescribed medications. Functional status assessment was carried out using a ten-item modified Barthel Index. Information on medical conditions and prescribed medications were obtained from homebased medical record or direct assessment by a trained healthcare worker. Data was analysed using descriptive statistics, Chi-square test for association between falls and risk x factors and finally multiple logistic regression for predictors of falls. The prevalence of falls was 30.5% and majority (96.5%) of fallers had no injury. Most falls (84.2%) occurred during the day and 63.2% occurred outside the house. The main reason for falls was due to slips (73.7%) and trips (17.5%), and the remaining due to dizziness. Falls occurred almost equally among the age groups, males and females, those married and those without spouses, the ethnic groups, education levels, various income groups, and those staying alone or with extended family. Bivariate analysis showed no significant associations between falls and the socio-demographic variables. There were also no significant associations between falls and the medical conditions of hypertension, diabetes, heart disease, hearing impairment, cancer, gastritis and stroke and prescribed medications. Bivariate analysis showed significant associations between falls and functional status, arthritis, asthma or chronic obstructive pulmonary disease, visual impairment and urinary incontinence. Finally, from the multivariate analysis, functional status was a predictor of falls among the study population.